Adoption of bovine somatotropin in the United States and implications for international trade of dairy products : a thesis presented in partial fulfilment of the requirement for the degree of Master of Agricultural Economics, Massey University, Palmerston North, New Zealand - Guthrie, Joseph William (Massey University, 1992)
Advancements in biotechnology have led to some of the most important changes in agriculture in this century. The development of synthetic bovine Somatotropin, a hormone which increases milk production from dairy cows, may have a significant impact on the dairy industry in the near future. While bovine Somatotropin, or bST, has been widely studied, its potential impacts, both on milk production and on the economics of the dairy industry, remain controversial. At this time, bST has not been approved for use in any of the developed countries. It appears that, for a variety of reasons, the United States would be the most likely to approve bST in the near future. If bST is approved in the us, and widely adopted by American farmers, it could increase milk production in the US significantly, although the exact magnitude of its effects are difficult to determine at this time. Another important factor in determining US milk production is the US government's dairy policy. The policy for 1991-1995 is contained in the recently passed 1990 Farm Bill. The dairy provisions in the 1990 Farm Bill will maintain the current support price for milk at its current level, regardless of how large dairy surpluses become. Together, the increase in milk production from bST along with a guaranteed minimum support price could lead to significant surpluses of dairy products in the US by 1995. Since the US has traditionally sold its dairy surpluses on the international market at subsidised prices, or simply given them away as food aid, a large increase in US surpluses could have a great impact on the international dairy market. Furthermore, because the 1990 Farm Bill was only passed recently, no studies have yet been published which address the impact of bST under the current policy environment or what effect this would have on the world dairy market. The objective of this study is to empirically estimate the impact of bST on us production, and determine the implications for international trade of dairy products. A five equation quarterly econometric model of the US dairy industry is used to forecast US production through 1995. Then the effects of bST use are incorporated into the model. The results show that if bST is adopted in the US as assumed, by 1995 surpluses of dairy products could rise to as much as 12 billion pounds. This surplus would be nearly as large as the record surpluses of the early 1980's, which caused unprecedented disturbances to the international dairy market. Thus, use of bST in the US could significantly increase the excess supply of dairy products in the world, and thereby lower prices, especially of butter and skim milk powder. New Zealand would be particularly vulnerable to any price reductions on the world dairy market. The European Community, which is the largest exporter of dairy products, may have to increase its own export subsidies to compete against the US. This, in itself could lead to even further turmoil in the world market.
Keywords: Bovine somatotropin; United States Dairying; Dairy products; Economic aspects